2005
DOI: 10.1111/j.1651-2227.2005.tb02104.x
|View full text |Cite
|
Sign up to set email alerts
|

The right ventricle in Fabry disease

Abstract: Aim: Left ventricular (LV) hypertrophy is a common feature in Fabry disease‐related progressive infiltrative hypertrophic cardiomyopathy and affects both men and women, but at different ages. To date, however, little is known about the role of right ventricular (RV) function in Fabry disease. Therefore, this study aimed to investigate the extent of RV involvement in patients with Fabry disease. Methods: Echocardiographic examination of the right and left ventricle was carried out in 129 patients (80 women and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Its aetiology may be a reduction in stroke volume and cardiac output, especially at stress induced by LV hypertrophy, increased left atrial pressure due to poor diastolic function, or both. Right ventricular involvement has also been suggested to have a role in this cascade (Kampmann et al 2005). Mean exercise capacity was 60% of the reference value, which is at the same level as observed earlier in Fabry disease (Bierer et al 2006).…”
Section: Efficiency Of Ert Regarding the Severity Of Fabry Diseasementioning
confidence: 82%
“…Its aetiology may be a reduction in stroke volume and cardiac output, especially at stress induced by LV hypertrophy, increased left atrial pressure due to poor diastolic function, or both. Right ventricular involvement has also been suggested to have a role in this cascade (Kampmann et al 2005). Mean exercise capacity was 60% of the reference value, which is at the same level as observed earlier in Fabry disease (Bierer et al 2006).…”
Section: Efficiency Of Ert Regarding the Severity Of Fabry Diseasementioning
confidence: 82%
“…RV involvement in FD has been evaluated in two previous studies by Palecek and Kampmann et al 19 20. Both could clearly document that RV involvement is common in patients with FD.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, in theory the RV should be involved in FD as well. Two recently published studies investigated RV involvement in FD using standard echocardiography in a cross-sectional design 19 20. Both studies clearly showed that RV involvement is a common finding in FD, and the RV involvement largely paralleled LV involvement when assessed with standard echo parameters 20…”
Section: Introductionmentioning
confidence: 98%
“…This mosaic cellular phenotype is due to random X-chromosome inactivation first described by Lyon [31,32]. Cardiac involvement is commonly seen in the classic AFD phenotype namely, LVH, valvular dysfunction, and conduction abnormalities [7][8][9][10]20,22,23,33]. Although these abnormalities are well described in male AFD patients, it is only recently that their contribution to morbidity in female heterozygotes has begun to be appreciated.…”
Section: Discussionmentioning
confidence: 95%